Analisa Sistem Informasi Akuntansi Dan Pengaruh Sosial Media Sebagai Media Promosi Penjualan Rotte Bakery Pekanbaru - Afrianti Kartika Putri; Septiana Srinandini; Muhammad Richard Ginting; Zul Azmi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study was to determine and analyze the accounting information system and the influence of social media as a promotional medium on the sales of Rotte Bakery, PekanBaru. The target object of this research is Rotte Bakery PekanBaru. This research uses a descriptive method with a qualitative approach with primary data obtained from observations and interviews with the director of the IT department and the marketing department at Rotte Bakery. Based on the results of observations and interviews, this study shows the results that the analysis of accounting information systems and the influence of social media as a promotional medium to increase sales at Rotte Bakery is very helpful for companies in running their business. The sales accounting information system developed by Rotte Bakery, namely Dreampost.id, aims for an ERP (Enterprise Resource Planning) system, there are several sections such as logistics, profit sharing and payroll, cashiers, and sales that have been collected into one in this application. With this application, it helps companies integrate their sales. In addition, social media also plays a role in increasing sales at Rotte Bakery. By making social media a promotional platform, sales at Rotte Bakery increased from 2019 by an average of 30-60%. This shows that social media is very influential on Rotte Bakery's marketing.